2020
DOI: 10.14748/isuvsme.v25i1.7211
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adenotomy/adenoidectomy on the respiration and occlusion in mouth-breathing children

Abstract: Introduction: Difficult nasal breathing is a common problem, which may be a result of multiple factors, leading to physiological disturbance and/or anatomical disorders of the nose and paranasal sinuses. One of the most frequent reasons in childhood age is adenoid hypertrophy. Aim: The aim of the current article is to determine the influence of adenotomy and adenoidectomy on the respiration and occlusion of children with difficult nasal breathing Materials and Methods: A total of 412 children, diagnosed with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…10 Mouth breathing was the second most common habit in the present study as well as in results reported by Aloumi et al 10 This may be due to the high prevalence of deviated nasal septum or adenoids in the general population. 14,15 The results of the present research show that the most prevalent temporomandibular joint disorder symptom observed is noise from TMJ (66%) followed by pain, and difficulty in mouth opening and the least common symptom seen was jaw getting stuck (24%). These results are in total accordance with the results of the study by Atsu et al and Chazopoulos et al who reported TMJ noises to be the most common, pain to be 2 nd most common followed by difficulty in jaw opening.…”
Section: Discussionmentioning
confidence: 63%
“…10 Mouth breathing was the second most common habit in the present study as well as in results reported by Aloumi et al 10 This may be due to the high prevalence of deviated nasal septum or adenoids in the general population. 14,15 The results of the present research show that the most prevalent temporomandibular joint disorder symptom observed is noise from TMJ (66%) followed by pain, and difficulty in mouth opening and the least common symptom seen was jaw getting stuck (24%). These results are in total accordance with the results of the study by Atsu et al and Chazopoulos et al who reported TMJ noises to be the most common, pain to be 2 nd most common followed by difficulty in jaw opening.…”
Section: Discussionmentioning
confidence: 63%